Direct and indirect role of non-coding RNAs in company with amyloid and tau protein in promoting neuroinflammation in post-ischemic brain neurodegeneration - Pluta, Ryszard (Frontiers in Cellular Neuroscience, 2025)
Post-ischemic brain neurodegeneration with subsequent neuroinflammation is a major cause of mortality, permanent disability, and the development of Alzheimer’s disease type dementia in the absence of appropriate treatment. The inflammatory response begins immediately after ischemia and can persist for many years. Post-ischemic neuroinflammation plays a dual role: initially, it is essential for brain repair and maintenance of homeostasis, but when it becomes uncontrolled, it causes secondary damage and worsens neurological outcome. Neuroinflammation is a complex phenomenon involving interactions between infiltrating immune cells from the peripheral circulation and resident immune cells in ischemic brain areas. This review focuses on the complex relationship between non-coding RNAs, amyloid accumulation, tau protein modifications, and the development of neuroinflammation in the post-ischemic brain. In particular, it clarifies whether the cooperation of non-coding RNAs with amyloid and tau protein enhances neuroinflammation and whether the vicious cycle of neuroinflammatory responses affects the production, behavior, and aggregation of these molecules. Ultimately, elucidating these interactions is critical, as they may contribute to resolving the phenomenon of post-ischemic brain neurodegenerative mechanisms. Furthermore, this review highlights the role of neuroinflammation as a functionally complex immune response regulated/mediated by transcription factors and cytokines. Additionally, it examines how the presence of non-coding RNAs, amyloid aggregation, and modified tau protein may shape the inflammatory landscape. This review aims to advance our understanding of post-ischemic neuroinflammation and its implications for long-term brain health.